Revisiting The Community and Service Oriented Policing (CSOP) System: Basis for Sustainable Peace and Order - De Lana, Darius Carreon; -De Lana, Marites Reyes; Dausan, Alrien Francisco; Villa, Elizabeth B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
The aimed of this study was to revisit the community and service-oriented policing (CSOP) system for sustainable peace and order. This study used survey methods in conjunction with descriptive study design. Police Stations 6 and 13 in the barangays of Batasan Hills, Commonwealth, and Payatas were used for the locale of the study. The study only looked at the age, gender, marital status, high-est level of schooling, classification, place of assignment for PNP members, and address of barangay officials and residents of the people who answered the survey. In the study of Martinez (2019) provided a survey questionnaire that was used as the research in-strument in this study. They used the mean and Pearson-r Correla-tion to examine the data. Three groups of respondents were asked to rate how well the Community and Service-Oriented Policing (CSOP) System strategies were being put into action. The strategies were evaluated in terms of how well they supported local chief ex-ecutives (LCEs), how well they provided police services, and how well they worked with the community. Out of the 279 people who willingly answered the survey, 267 were found. Some went through Google Forms, while others were given hard copies. The Philippine National Police started to work together with mayors, local chief executives, and the people who live in the area to improve the way they provide police services thus, local chief executives are in full support to the implementation of the community and service-oriented policing system as they are regularly coordinating with the provincial/regional office of the National Police Commission, they are ready to give funds as their support to the implementation of the community and service-oriented policing for the betterment of their constituents in the municipality/city as these were based on the problems that people in the community had pointed out.